Assessment of criteria – rich rankings for environmental policy making. (12th July 2011) - Yeralan, Sencer; Ozdoglar, Mehmet Rasit; Azizoglu, Meral
This paper illustrates the use of mathematical programming techniques to extract more information out of composite indexes (e.g., the EPI-2008) that would assist decision makers. While recognising the qualitative aspects of such decision making, in order to support and guide the policy making process, we develop analytical tools to assist the process. We carefully delineate our models to be limited only to the provable quantitative properties of the available objective data. However, such data are processed into more meaningful statements concerning the available options. Specifically, using EPI-2008, meaningful mathematical models that shed further light onto the country sustainability measures are developed. The models may be used to determine which criteria must be emphasised if the composite score or the rank of a given country is to be improved.